Impactos ambientais do eucalipto: um estudo comparativo entre Brasil e Portugal - Teixeira, Georgia (2023)
Silviculture is the activity of planting and exploiting forests for commercial purposes. In both Brazil and mainland Portugal, Eucalyptus ssp., originally from Australia, is the most widely cultivated exotic species in reforestation due to its easy adaptability to soil and climatic conditions and its high productivity over short rotation periods, making it a key commodity in the forestry sector in both countries. Eucalyptus cultivation was consolidated in Brazil and Portugal as part of public reforestation policies to supply large consumers of raw forestry materials in the mid-20th century. Despite their economic dynamism, eucalyptus planted forest is the subject of controversial discussions on its environmental impacts. On the one hand, it is considered an activity that helps mitigate anthropogenic pressure on native forests. On the other hand, it is a monoculture commonly associated with adverse impacts, mainly on water, soil, biodiversity and land concentration. From the perspective of socio-environmental geography, the main aim of this thesis is to undertake a comparative study of the forestry environmental impacts in Brazil and Portugal, using the municipality of João Pinheiro (Minas Gerais) and the NUTS III AVE (Northwest Portugal) as spatial cut-off points. The methodological effort focused on a bibliographical review, documentary research and the socioenvironmental characterization of these territories, fieldwork and technical visits. The results obtained were summarized by applying the SWOT matrix tool. Due to its simplicity of construction, the matrix proved to be a useful tool for organizing the strengths, weaknesses, threats and opportunities of eucalyptus forestry. However, it provided a comprehensive view of its components, and therefore offered a superficial analysis of the environmental impacts, which makes it limiting when it comes to comparative parameterization of spatial data, activities and environmental impacts. The matrix can be combined with other methods of analysis, which can enable a more effective assessment and a better understanding of the dynamics of the geographical space and the territorial implications of eucalyptus forestry, especially with regard to the cumulative impacts (additive and synergistic). In this sense, it can be used as an auxiliary tool for public and private decision-making aimed at territorial management in environmental studies and for promoting integrated management for the sustainability of eucalyptus silviculture. It was concluded that eucalyptus planted forests have had negative impacts on the environmental systems of João Pinheiro and the NUTS III AVE. These impacts are part of landscape matrices where both natural diversity and past human activity are multiple, so that the sector has become part of the set of vectors inducing the reorganization of the territory and the territorial division of labour. In this context, it was observed that the insertion of eucalyptus planted forests in the areas resulted in the reinforcement of pre-existing impacts, such as increased deforestation and the induction of new impacts, such as the introduction of monoculture, the agroindustry and their effects.